State of the art of surgical robotics - Pott, Peter Paul; Köpfle, Andreas; Wagner, Achim; Badreddin, Essameddin; Männer, Reinhard; Scharf, Hanns-Peter; Schwarz, Markus (Perspective in image-guided surgery, 2004)
This work describes the worldwide state of the art concerning the development of robot-aided operative medicine. It is based on literature-, proceedings- and internet-research. 84 robotic systems are presented briefly by describing applications workgroups, project status and reference. The examination of the international research and development in the field of robotic applications in medicine shows a wide distribution in different areas of medicine. Only a few systems can be used clincally.